Analysis of PM10 in Kuala Terengganu by Instrumental Neutron Activation Analysis - Norhayati, Mohd Tahir; Poh, Seng Chee; Suhaimi, Hamzah; Khalik, Hj Wood; Shamsiah, Abd. Rahman; Wee, Boon Siong; Nazaratul Ashifa, Abdullah Salim; Suhaimi, Elias (UKM Publisher, 2008)
Instrumental neutron activation analysis was used for the determination of trace elements in airborne particulate matter (PM10) for air pollution monitoring. For the collection of air samples, the PM10 high volume sampler unit and Whatman 41 cellulose filter papers were employed. Samples were collected at 13 selected sampling sites covering areas in the city center, inner and outer city of Kuala Terengganu during the month of March 2005. The average PM10 was 69.64 μgm-3, 83.58 μgm-3 and 72.22 μgm-3 for sampling stations located in the city center, inner and outer city of Kuala Terengganu, respectively. It was found that the mass of air particles in the study area was higher compared to Bangi and Kuala Lumpur. Chemical analysis of selected elements (Al, Fe, Cu, Pb, V, Mn, Zn, Cr, As Cd), ionic species (Na+, SO4 2-, Cl-, NH4 +,Mg2+, K+ , Ca2+) and some rare earth elements (REE) were included in this study. In general, most of the average concentration of trace elements in the city center sampling stations was generally higher than the inner and outer city sampling stations. The concentrations of trace elements in sampling stations follow the general trend of Al>Fe>Zn>Cu>Mn>Pb>V>Cr>As>Ni>Cd. The elements concentration ranged from 680-2119 ngm-3, 170-1132 ngm-3, 8.13-122.4 ngm-3, 8.48-77.3 ngm-3, 7.68-14.4 ngm-3, 1-90.4 ngm-3, 1.47-3.25 ngm-3, 1.43-5.03 ngm-3, 1.15-4.45 ngm-3, 0.24-3.75 ngm-3 and 0.28-1.36 ngm-3, respectively.